Novel CaF2 Nanocomposites with Antibacterial Function and Fluoride and Calcium Ion Release to Inhibit Oral Biofilm and Protect Teeth - Heba Mitwalli; Abdulrahman A. Balhaddad; Rashed AlSahafi; Thomas W. Oates; Mary Anne S. Melo; Hockin H. K. Xu; Michael D. Weir (Journal of Functional Biomaterials, 2020)
(1) Background: The objective of this study was to develop a novel dental nanocomposite containing dimethylaminohexadecyl methacrylate (DMAHDM), 2-methacryloyloxyethyl phosphorylcholine (MPC), and nanoparticles of calcium fluoride (nCaF2) for preventing recurrent caries via antibacterial, protein repellent and fluoride releasing capabilities. (2) Methods: Composites were made by adding 3% MPC, 3% DMAHDM and 15% nCaF2 into bisphenol A glycidyl dimethacrylate (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA) (denoted BT). Calcium and fluoride ion releases were evaluated. Biofilms of human saliva were assessed. (3) Results: nCaF2+DMAHDM+MPC composite had the lowest biofilm colony forming units (CFU) and the greatest ion release; however, its mechanical properties were lower than commercial control composite (p < 0.05). nCaF2+DMAHDM composite had similarly potent biofilm reduction, with mechanical properties matching commercial control composite (p > 0.05). Fluoride and calcium ion releases from nCaF2+DMAHDM were much more than commercial composite. Biofilm CFU on composite was reduced by 4 logs (n = 9, p < 0.05). Biofilm metabolic activity and lactic acid were also substantially reduced by nCaF2+DMAHDM, compared to commercial control composite (p < 0.05). (4) Conclusions: The novel nanocomposite nCaF2+DMAHDM achieved strong antibacterial and ion release capabilities, without compromising the mechanical properties. This bioactive nanocomposite is promising to reduce biofilm acid production, inhibit recurrent caries, and increase restoration longevity.